2014
DOI: 10.15835/buasvmcn-hort:10607
|View full text |Cite
|
Sign up to set email alerts
|

Women entrepreneurship in Romania: a regional evaluation

Abstract: The study aims to asses overall satisfaction of the initiative for becoming an entrepreneur among women in Romania. The research was conducted in the Regions of North East, North West and West, on a sample of 602 women entrepreneurs. The research method chosen was the sociological survey. Almost three quarters of the respondents declare to be satis ied having opened a business. The degree of satisfaction regarding this decision is associated with age, education and family income. The main motivations identi ie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The minimum price quoted for a jar of honey was R$2.00 (∼U$0.40) and the maximum was R$100.00 (∼U$20.40); for stingless bees, prices were quoted between R$ 2.00 (U$ 0.40) and R$ 300.00 (∼U$ 61.20). Honey from stingless bees has a significantly higher price than honey from A.mel ıfera (Pocol and Teselios, 2012;Ismaiel et al, 2014;Zuccato et al, 2017) and can reach US $100/kg, (Shadan et al, 2018), but there is little information on what consumers think about it in the current literature. The production of stingless bee honey is usually on a small scale and there are not many products in the market; thus, it is not a usual consumed product, and there are several types of stingless bee honey ( Avila et al, 2018), which may explain the high range of prices observed herein.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum price quoted for a jar of honey was R$2.00 (∼U$0.40) and the maximum was R$100.00 (∼U$20.40); for stingless bees, prices were quoted between R$ 2.00 (U$ 0.40) and R$ 300.00 (∼U$ 61.20). Honey from stingless bees has a significantly higher price than honey from A.mel ıfera (Pocol and Teselios, 2012;Ismaiel et al, 2014;Zuccato et al, 2017) and can reach US $100/kg, (Shadan et al, 2018), but there is little information on what consumers think about it in the current literature. The production of stingless bee honey is usually on a small scale and there are not many products in the market; thus, it is not a usual consumed product, and there are several types of stingless bee honey ( Avila et al, 2018), which may explain the high range of prices observed herein.…”
Section: Resultsmentioning
confidence: 99%
“…Ferreira et al [23] pointed out the economic effects of the associations in terms of the impact on employment regardless of nationality [24], while Androulidakis and Harizanis [25] emphasized the importance of the associations in organized beekeeping education, technical support, providing relevant statistical data [26], clarifying or interpreting legislation [27], strengthening entrepreneurial orientations [28] and marketing the performance of honey and honey products [29], market positioning [30] and more. Pocol et al [31] point out the importance of beekeepers' associations in establishing cooperation with other beekeepers, while Popa et al [27] point out that associations should cooperate with other beekeeping associations, but also with other companies, in order to modernize beekeeping. According to Mushonga et al [32], local authorities should promote the establishment of beekeeping associations as the findings show that the beekeepers' operations should be supported by education and training.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They are used by humans for centuries for various purposes, making them as interesting subject for research and analysis. Romania is an important producer of potatoes and tomatoes, in accordance with favorable natural and climatic conditions for their growing, as well as long tradition (Pocol, Sahli, 2010;Soare et al, 2017).…”
Section: Introductionmentioning
confidence: 99%